Evaluation of Contour Cultivation and Nutrient Management Practices for Maize-Wheat Productivity on Sloping lands of Rainfed Submontane Region of Jammu - K.R. Sharma; Sanjay Arora (Journal of Soil and Water Conservation, 2022)
In order to evaluate the land management including contour cultivation across the slope and use of integrated nutrient management practices for improving crop yields in the rainfed foothill region on farm Jammu, on farm experiments were conducted. Soil moisture storage increased by 30.2 and 49.4 per cent respectively during maize and wheat under contour cultivation across the slope along with use of recommended levels of nutrients through organic and inorganic sources as compared to farmers practice. There was 49.4 and 59.3 per cent increase in maize and wheat grain yield respectively under the imposed treatments compared to the farmers practice. Also, the imposed practices resulted in increased N, P, K content in grain and straw of maize and wheat. The increase in N content in maize and wheat grain was to the tune of 35.6 and 25.5 per cent in imposed treatments as compared to the farmers practice.